0143 The Kent, Surrey And Sussex Children's Simulation Collaboration. (1st November 2014) - Mishra, Amit; Parry, Martin G; Kalidasan, Varadarajan; Mukhopadhyay, Somnath
Abstract : Introduction: We are developing a collaborative project for paediatric healthcare technology enhanced learning (TEL) within our region, through active co-operation and networking between a number of NHS organisations within Kent, Surrey and Sussex. Our goal was to ensure that the project delivered TEL educational opportunities to all healthcare professionals involved with a paediatric patient's journey from primary care, to secondary care, and back to the community, maintaining the focus on safe, effective patient-centred care. We will present our experience of the challenges we have faced in trying to develop this project and are keen to work with other networks across the UK. Methodology: Following a scoping exercise we identified 5 core areas of TEL delivery which we aimed to address within our region using a variety of technologies including paediatric simulation-based education: Development of Simulation Instructor Faculty Fixed base simulation Mobile simulation across satellite sites Software-delivered e-Learning Distance-learning initiatives The initial phase of the project was to develop a central hub at the Royal Alexandra Children's Hospital, Brighton and then extend the collaboration into our partner organisations. Outcomes: An educational grant has been received from Health Education Kent, Surrey and Sussex to develop the collaborative paediatric simulation network within our region. The development of the hub phase is in progress and we are working with collaborating organisation to produce well-defined spoke linkages to the core group of paediatric simulation faculty at the RACH. We will present an overview of our experiences in setting up this collaborative project and discuss the challenges we continue to face in promoting simulation-based education across the region. Potential Impact: Collaborative TEL networks can help promote multi-professional learning amongst organisations and professionals advancing the delivery of safe, patient-centred paediatric healthcare.